2008
DOI: 10.1029/2007ja012894
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of escaping ions produced by non‐specular reflection at the stationary quasi‐perpendicular shock front

Abstract: [1] Field-aligned and gyrophase bunched ion beams are observed in the foreshock of the Earth bow shock. One of the mechanisms proposed for their production is non-specular reflection at the shock front. We study the distributions which are formed at the stationary quasi-perpendicular shock front within the same process which is responsible for the generation of reflected ions and transmitted gyrating ions. The test particle motion analysis in a model shock allows one to identify the parameters which control th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 60 publications
2
18
0
Order By: Relevance
“…They have shown that all these populations were produced by ion gyration and reflection at the shock front. This finding was later supported by theoretical studies [ Gedalin et al , ]. Oka et al [] suggested that backstreaming ions are produced by multiple interaction of the incident ions with the supercritical shock transition.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…They have shown that all these populations were produced by ion gyration and reflection at the shock front. This finding was later supported by theoretical studies [ Gedalin et al , ]. Oka et al [] suggested that backstreaming ions are produced by multiple interaction of the incident ions with the supercritical shock transition.…”
Section: Introductionmentioning
confidence: 73%
“…It was shown, however, that such specular reflection requires too high cross‐shock potentials [ Wilkinson and Schwartz , ] and that at low initial temperatures the reflection occurs behind the ramp due to the gyration in the increased magnetic field [ Gedalin , ]. At higher temperatures, some of the incident ions were shown to be reflected at low Mach numbers and low magnetic compressions [ Gedalin et al , ]. Most incident ions are directly transmitted downstream upon crossing the ramp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible reason for the decrease in normalized potential with increasing M A is that the increase in cross‐shock potential may prove too strong to allow ion reflection [ Wilkinson and Schwartz , 1990] and so reduce the number and energy of the directly transmitted ions [ Gedalin , 1996a]. However, the number of ions escaping would be expected to increase with increasing Mach number [ Gedalin et al , 2008], to provide the required dissipation to prevent overturning.…”
Section: Discussionmentioning
confidence: 99%
“…Field‐aligned beams are generally seen upstream of Earth's bow shock where 40° ≤ θBN ≤ 70° [see, for example, Paschmann et al ., ]. A number of works have studied the mechanisms by which ions can escape upstream of quasi‐perpendicular shocks [see, for example, Burgess , ; Gedalin et al ., ].…”
Section: Introductionmentioning
confidence: 99%